Espaces vécus et imaginés des rencontres amoureuses aux Émirats arabes unis - Laure Assaf (EchoGéo)
The love relationships of young adults in the United Arab Emirates often take on an important spatial dimension, whether they are lived or fictional. The recent urban space of Emirati cities crystallizes indeed social norms that are reinforced by the coexistence of varied populations. From the parking lots to the shopping malls, young adults use the potentialities of space to emancipate themselves, although temporarily, from these norms, while playing on the boundary between transgression and respectability, but also while looking for other horizons in the imagined spaces of their cultural productions, blogs and short movies, or within online social networks.